1996
DOI: 10.1111/j.1467-9280.1996.tb00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Gesture, Speech, and Lexical Access: The Role of Lexical Movements in Speech Production

Abstract: 111 n ic*ithiri-siibjects design t h t w r i e d idietlier speakers ic-ere n l l o w d to gestirre arid the difficiilty of lexicol nccess, spenkers were i*icleotoped ns they described otiitiintetl nctiori cortooris to n listcrier. IVIieri speakers were perttiitred to gestirre, they gestiirrd riiore oJeti diiritig pliroses with spatial coriteiit thari cliiririg phrcises witli other coritetit. Speech with spatiol coriterit itws less Jiierit itheti speakers coriid iiot gestirre tlinri u-lieii they coirld gesture;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
374
5
10

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 386 publications
(407 citation statements)
references
References 22 publications
18
374
5
10
Order By: Relevance
“…Speakers have been found to gesture more when describing spatial content (Rauscher et al, 1996) and when such content must be recalled from memory, leading researchers to concluded that gesture either helps to maintain spatial information in spatial working memory (Wesp et al, 2001;De Ruiter, 1998) or that it activates key spatio-motoric information in the semantic representation of the searched-for word (Morsella and Kraus, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Speakers have been found to gesture more when describing spatial content (Rauscher et al, 1996) and when such content must be recalled from memory, leading researchers to concluded that gesture either helps to maintain spatial information in spatial working memory (Wesp et al, 2001;De Ruiter, 1998) or that it activates key spatio-motoric information in the semantic representation of the searched-for word (Morsella and Kraus, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…6 More recently, Graham and Hayward (1975) analyzed the speech of five speakers who were prevented from gesturing as they described abstract line drawings, and concluded that "… elimination of gesture has no particularly marked effects on speech performance" (p. 194). On the other hand, Rimé (1982) and Rauscher, Krauss and Chen (1996) have found that restricting gesturing adversely affects speech. See for a review of the relevant studies.…”
Section: Lexical Retrievalmentioning
confidence: 99%
“…However, the ability to represent and communicate about space is not limited to verbal expressions. Speakers often gesture as they speak, especially when they talk about space (Rauscher, Krauss, & Chen, 1996). Recent research has shown that speech and cospeech gesture form an integrated system (Bernardis & Gentilucci, 2006;Clark, 1996;Kendon, 2004;McNeill, 1992McNeill, , 2005 and that they develop in close relation to each other during childhood (Bates, 1976;Capirci, Iverson, Pizzuto, & Volterra, 1996;McNeill, 1992McNeill, , 2005Nicoladis, Mayberry, & Genesee, 1999;Ö zçalişkan & Goldin-Meadow, 2005).…”
mentioning
confidence: 99%